Предмет: Математика,
автор: hastay6
помогите!!! срочно даю 30 балов
Приложения:
Ответы
Автор ответа:
0
Пошаговое объяснение:
2) Не видно
3)(x-1)^2 + (x-2)^2 = 2x^2 + 7
Раскроем скобки
x^2 - 2x + 1 + x^2 - 4x + 4 = 2x^2 + 7
2x^2 - 6x + 5 = 2x^2 + 7
2x^2 - 6x + 5 - 2x^2
-6x = 5
x = -(5/6)
4)(-8 - 4)(-8+4) - (-8+4)^2
(-12)(-4) - 16
-48 - 16
Ответ: -64
Похожие вопросы
Предмет: Математика,
автор: dashakaterina2010
Предмет: Алгебра,
автор: annatol08
Предмет: Физика,
автор: davidovaelona11
Предмет: Алгебра,
автор: Black0Cube
Предмет: Обществознание,
автор: golubenko1985